Escutas, memórias e subjetividades: acervo Sesc Memórias e os usos da história oral em contextos - Santos, Carla Lira Mendes dos (2022)
The research “Listenings, memories and subjectivities: The collection Sesc Memories and oral history usages in educational contexts” comes from works developed by the interviews about oral history which compose the collection of Sesc Memories, São Paulo Sesc Memory Center. From the conception of the curriculum as a cultural development and its acts beyond formal education, we are invited to think about the strength of narratives built in an informal educational environment which contribute to educational actions. By inserting them in a debate about the curriculum, we can observe the development of a social and cultural network, in which the aspects of people's experiences are known as key to an educational process. Considering this scenery, we intend to comprehend how the narrative records of such interviews can take part in broadcasting institutional memories, ensuring the articulation of knowledge produced and the dissemination beyond institutional borders. Through a qualitative approach, a metodologic development of this work is based on an ex-post facto research, by the light of documentation, we intend to capture in those narratives the hypothesis of the realization of educational actions considering memory as a value worth being cultivated. In order to achieve it, we take into consideration the concepts of experience and subjectiveness in the informal educational area as part of a theoretical support. In this way, it is proposed to analyze the relationships woven by the interviewees about their experiences and experiences, recorded in the narratives stored in the collection. These records allowed reflections on the relevance of debates on curriculum and culture in an institution that promotes non-formal and permanent education as an integral part of its programming. And as a result, the contribution of a critical evaluation of the curriculum-culture relationship that involves the memory activities carried out at Sesc SP stands out